(untitled) (Modern education and development, 2024)
Phraseological units (PUs) with onomastic components, also known as eponyms, are fixed expressions that incorporate proper names or their derivatives. This study investigates PUs with onomastic components in English and Uzbek, exploring their linguistic structure, cultural significance, and comparative aspects. The analysis reveals that both English and Uzbek employ PUs with onomastic components to convey a wide range of meanings and cultural references. These expressions often reflect historical events, mythological figures, or cultural touchstones, providing insights into the cultural values and beliefs of each language community.